A study about the relationship between time orientation factors and procrastination among the students of Human Resource Management in UiTM Kampus Bandaraya Melaka - Mohd Kasim, Nurul Sharmeen (2015)
The main purpose of this study is to determine the relationship between time orientation factors and procrastination among students of Human Resource Management in UiTM Kampus Bandaraya Melaka. The independent variables of this study consist of the elements of time perspective orientation which is Past-Positive, Past-Negative, Present- Hedonistic, Present-Fatalistic and Future Oriented. There are 260 respondents from the students of Human Resource Management in UiTM Kampus Bandaraya Melaka. This study use descriptive analysis and correlational analysis research method to find the relationship between dependent variable and independent variables. Furthermore, the researcher used questionnaire as the method to collect all the data from respondents in accomplishing the research objectives. Overall in this study, the findings indicate that the level of procrastination among the students is moderate meanwhile only past-negative orientation has a minor relationship with procrastination.